2019
DOI: 10.1021/acs.analchem.9b02446
|View full text |Cite
|
Sign up to set email alerts
|

A Generic Liquid Chromatography−Tandem Mass Spectrometry Exposome Method for the Determination of Xenoestrogens in Biological Matrices

Abstract: We are constantly exposed to a variety of environmental contaminants and hormones, including those mimicking endogenous estrogens. These highly heterogeneous molecules are collectively referred to as xenoestrogens and hold the potential to affect and alter the delicate hormonal balance of the human body. To monitor exposure and investigate potential health implications, comprehensive analytical methods covering all major xenoestrogen classes are needed but not available to date. Herein, we describe a liquid ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 49 publications
0
29
1
Order By: Relevance
“…The mean (maximum) concentration of OTA and ZEN were relatively lower in this study compared to previously reported data from Cameroon [30] and Nigeria [38]. However, the extremely high detection rate of 82% for total ZEN is somehow worrisome given the high xenoestrogenic potential of ZEN and its phase I biotransformation products [43]. Recent studies further highlighted that ZEN is prone to synergistic mixture effects [44,45] and able to pass the placental barrier and thus exposure of mothers is likely to result in in utero exposure of the unborn child [46].…”
Section: Discussioncontrasting
confidence: 79%
“…The mean (maximum) concentration of OTA and ZEN were relatively lower in this study compared to previously reported data from Cameroon [30] and Nigeria [38]. However, the extremely high detection rate of 82% for total ZEN is somehow worrisome given the high xenoestrogenic potential of ZEN and its phase I biotransformation products [43]. Recent studies further highlighted that ZEN is prone to synergistic mixture effects [44,45] and able to pass the placental barrier and thus exposure of mothers is likely to result in in utero exposure of the unborn child [46].…”
Section: Discussioncontrasting
confidence: 79%
“…The polar analytes TeA, AA-III and AOH-and AME-sulfates, as well as the included perylene quinones, demonstrated better peak shapes with basic eluents. However, the overall signal-to-noise ratio was most favorable with 0.3 mM NH 4 F as eluent A (Preindl et al 2019;Yanes et al 2011). Despite the still interfering matrix suppression in fecal samples, the overall performance was most suitable using this eluent A and MeOH as eluent B.…”
Section: Development Of the Analytical Methodsmentioning
confidence: 99%
“…Table S3). ZEN was recently shown to cross the placental barrier and exhibit synergistic toxic effects with other xenoestrogens (Vejdovszky et al, 2017a,b;Preindl et al, 2019;Warth et al, 2019). Hence, this finding needs to be confirmed in further surveys.…”
Section: Proof-of-principle Application Of the Integrated Quechers-spmentioning
confidence: 92%